ROP GTPase‐mediated auxin signaling regulates pavement cell interdigitation in Arabidopsis thaliana. Issue 1 (20th October 2014) - Lin, Deshu; Ren, Huibo; Fu, Ying
Abstract In multicellular plant organs, cell shape formation depends on molecular switches to transduce developmental or environmental signals and to coordinate cell‐to‐cell communication. Plants have a specific subfamily of the Rho GTPase family, usually called Rho of Plants (ROP), which serve as a critical signal transducer involved in many cellular processes. In the last decade, important advances in the ROP‐mediated regulation of plant cell morphogenesis have been made by using Arabidopsis thaliana leaf and cotyledon pavement cells. Especially, the auxin‐ROP signaling networks have been demonstrated to control interdigitated growth of pavement cells to form jigsaw‐puzzle shapes. Here, we review findings related to the discovery of this novel auxin‐signaling mechanism at the cell surface. This signaling pathway is to a large extent independent of the well‐known Transport Inhibitor Response (TIR)–Auxin Signaling F‐Box (AFB) pathway, and instead requires Auxin Binding Protein 1 (ABP1) interaction with the plasma membrane‐localized, transmembrane kinase (TMK) receptor‐like kinase to regulate ROP proteins. Once activated, ROP influences cytoskeletal organization and inhibits endocytosis of the auxin transporter PIN1. The present review focuses on ROP signaling and its self‐organizing feature allowing ROP proteins to serve as a bustling signal decoder and integrator for plant cell morphogenesis. <inline-graphic xlink:href="ark:/27927/pgh30vxb9dw" content-type="jipb12281-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> Deshu Lin